Spectroscopic Study of the Interaction of DNA with the Linker Histone H1 from Starfish Sperm Reveals Mechanisms of the Formation of Supercondensed Sperm Chromatin. Issue 5 (11th July 2012) - Chikhirzhina Chikhirzhina, Elena Elena; Starkova Starkova, Tatyana Tatyana; Kostyleva Kostyleva, Elena Elena; Polyanichko Polyanichko, Alexander Alexander
Abstract : The interaction of the linker histone H1Z from the sperm chromatin of starfish Asterias amurensis with DNA was studied by spectroscopic and thermodynamic approaches. It has been shown that at the physiological conditions the interaction of the H1Z with DNA results in more compact structures compared to complexes of DNA with somatic histone H1. The typical profile of the DNA melting curves reveals two peaks attributed to the bound and unbound DNA. It has been shown that H1Z from starfish sperm stabilizes DNA to a greater extent compared to the somatic H1. It is possible that the presence of the additional α —helical segments within the C-terminal part of the H1Z typical for the linker histones from echinoderm sperm facilitates the protein-protein interactions which in turn stimulate cooperative binding of the histones to DNA, resulting in the formation of the supercompact sperm chromatin.